2015
DOI: 10.1002/14651858.cd008005.pub4
|View full text |Cite
|
Sign up to set email alerts
|

Sapropterin dihydrochloride for phenylketonuria

Abstract: al. Spanish BH4-responsive phenylalanine hydroxylase-deficient patients: evolution of seven patients on long-term treatment with tetrahydrobiopterin.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(7 citation statements)
references
References 43 publications
(39 reference statements)
0
6
0
Order By: Relevance
“…A subset of patients with PKU benefit from adjunctive treatment with pharmacological doses of tetrahydropterin (BH4) or sapropterin hydrochloride (178). Robust evidence from two systematic reviews demonstrates that BH4 is effective in reducing blood Phe concentrations and in increasing the Phe “tolerance” in BH4-responsive PKU patients (179, 180). Long-term treatment with sapropterin of such responsive patients with PKU also appears to improve Phe tolerance and may allow patients to discontinue highly restrictive diets (181).…”
Section: Case Vignettesmentioning
confidence: 99%
“…A subset of patients with PKU benefit from adjunctive treatment with pharmacological doses of tetrahydropterin (BH4) or sapropterin hydrochloride (178). Robust evidence from two systematic reviews demonstrates that BH4 is effective in reducing blood Phe concentrations and in increasing the Phe “tolerance” in BH4-responsive PKU patients (179, 180). Long-term treatment with sapropterin of such responsive patients with PKU also appears to improve Phe tolerance and may allow patients to discontinue highly restrictive diets (181).…”
Section: Case Vignettesmentioning
confidence: 99%
“…A smallscale study from Brazil, encompassing 18 patients, found six (33.3%) BH 4 -responders . As the prevalence of BH 4 responsiveness has been variable in different studies (Somaraju & Merrin, 2015), we cannot make any assertion concerning the probability of the figures from our PAH genotyping study and Nalin et al (2011) combined Phe and BH 4 loading test study to be confirmed in future BH 4 loading tests of our PKU population.…”
Section: Discussionmentioning
confidence: 71%
“…This is the first time that changes in protein equivalent intake from protein substitute with BH4 treatment have been assessed systematically, although other systematic reviews or meta-analyses have investigated the effects of BH4 treatment on blood Phe control and dietary Phe tolerance [ 56 , 57 , 58 ]. We have demonstrated that PKU patients with long-term BH4 responsiveness had a significant increase in dietary Phe and natural protein intake when on BH4 treatment.…”
Section: Discussionmentioning
confidence: 99%